Hepatitis B Virus Infection Is a Risk Factor for Periprosthetic Joint Infection Among Males After Total Knee Arthroplasty: A Taiwanese Nationwide Population-Based Study. Issue 22 (May 2016) - Kuo, Shu-Jui; Huang, Po-Hua; Chang, Chien-Chun; Kuo, Feng-Chih; Wu, Cheng-Ta; Hsu, Horng-Chaung; Lin, Che-Chen
Abstract : Abstract: Periprosthetic joint infection (PJI) is a grave complication that can affect patients undergoing total knee arthroplasty (TKA). In this study, we aim to determine whether hepatitis B virus (HBV) infection is a risk factor for PJIs. All patients (1184 males, 3435 females) undergoing primary TKA in Taiwan from 2001 to 2010 were recruited for analysis. The incidence of PJI was 523 among the males with HBV infection and 110 among the males without HBV (per 10, 000 person-years, P < 0.001). The males with HBV infection had a 4.32-fold risk of PJI compared with the males without HBV. HBV infection and diabetes were the risk factors for PJI among males. The incidence of PJI was 58.8 among the females with HBV infection and 75.2 among the females without HBV (per 10, 000 person-years, P = 0.67). The risk of PJI was higher for the males with HBV infection than for the males without 0.5 to 1 year after TKA (hazard ratio [HR] = 18.7, 95% confidence interval (CI) = 1.90–184) and >1 year after TKA (HR = 4.80, 95% CI = 1.57–14.7). HBV infection is a risk factor for PJI after TKA among males.